2019
DOI: 10.1186/s12969-019-0371-0
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography in children: a reliable tool for differential diagnosis of peripheral microvascular dysfunction and Raynaud’s phenomenon?

Abstract: Background Infrared Thermography (IRT) has been used for over 30 years in the assessment of Raynaud Phenomenon (RP) and other peripheral microvascular dysfunctions in adults but, to date, very little experience is available on its use in children for this purpose. The first aim of the study was to assess reproducibility of thermographic examination after cold exposure by comparing inter-observer agreement in thermal imaging interpretation. The secondary aim was to evaluate whether IRT is reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Similar results were obtained in [2,60]. Recent studies explored the possibility to classify RP patients based on their hands' temperature in baseline condition [61,62]. Horikoshi et al demonstrated that the baseline nail fold temperature was significantly lower in RP patients than in controls [48].…”
Section: Comparisons With Previous Studies and Discussion On Machine ...supporting
confidence: 55%
“…Similar results were obtained in [2,60]. Recent studies explored the possibility to classify RP patients based on their hands' temperature in baseline condition [61,62]. Horikoshi et al demonstrated that the baseline nail fold temperature was significantly lower in RP patients than in controls [48].…”
Section: Comparisons With Previous Studies and Discussion On Machine ...supporting
confidence: 55%
“…Typically, image processing includes selection of areas of interest and possibly temperature gradients. The use of temperature gradients from acral to more proximal parts of the hand depends on the type of RP in question, as the distal–dorsal difference has been shown to be able to distinguish pRP from RP secondary to SSc [ 13 , 30 ]. However, gradients are not necessarily a good predictor of the condition where structural tissue changes are not a prominent part of the condition such as in VWF [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of the image processing for both laser Doppler methods and thermographic imaging is that it is easily comprehensible and simple to perform. Although a study suggested systematic differences between observers [ 12 ], another study reported a good inter-rater reliability in thermographic imaging [ 30 ]. Accordingly, the disadvantages of this type of image processing are the inter-observer difference, the time consumption, and the need for image analysis training.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Thermography has been used to diagnose and evaluate several diseases that cause changes in local body temperature, including Raynaud’s phenomenon, scleroderma, burns, and diabetic feet. 10 11 Inflammation, infection, or malignancy can cause a local temperature rise that can be detected by thermal imaging. Thermography has also emerged as another non-invasive imaging tool for evaluating arthritis in that it reflects increased pathological blood flow associated with inflamed joints.…”
Section: Introductionmentioning
confidence: 99%